Implementation of Deep Learning Approach in Learning Innovation at Madrasah Ibtidaiyah Negeri 8 West Aceh - Rauzatul Jannah; Rina Rahmi; Rusdy Iskandar (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan UIN Raden Fatah, 2025)
This study aims to examine deep learning-based learning innovations at MIN 8 Aceh Barat using a descriptive qualitative approach and data triangulation method. Data were collected through interviews, observations, and documentation to obtain a comprehensive picture of teachers' understanding, learning implementation, and obstacles in applying deep learning. The results show that teachers understand deep learning as an approach emphasizing in-depth conceptual understanding, active student engagement, and the development of critical and creative thinking skills. However, its classroom application remains uneven due to limited formal training and varying teacher competencies. Many teachers are self-taught, resulting in inconsistent implementation. MIN 8 Aceh Barat has provided various learning media that support interactive and meaningful learning. The madrasah also plans technical guidance (bimtek) programs on deep learning, artificial intelligence (AI), and coding through the Teacher Working Group (KKG) and Subject Teacher Working Group (MGMP) forums to enhance teacher capacity. This study provides a novel contribution by highlighting the contextual challenges and readiness of Islamic educational institutions in implementing deep learning, emphasizing the urgent need for structured and sustainable training to strengthen pedagogical innovation in the era of digital transformation.